Mechanistic roles for calcium and vitamin D in the regulation of body weight - Soares, Mario; Muhardi, Leilani; Kurpad, A.; Chan She Ping-Delfos, Wendy; Piers, L. (Wiley-Blackwell Publishing Ltd., 2012)
Low intakes of calcium and inadequate vitamin D status often cluster with higher prevalence rates of obesity. Consequently, there has been much interest in the mechanisms by which calcium and vitamin D could regulate body weight and adiposity. This review has focused on randomized controlled trials (RCTs) that have manipulated these nutrients and studied pathways of energy balance. Overall, there is consistent evidence that calcium and vitamin D increase whole body fat oxidation after single and multiple meals, and that calcium promotes a modest energy loss through increased faecal fat excretion. The evidence is equivocal for a greater diet-induced thermogenesis, increased lipolysis, suppression of key lipogenic enzymes, decreased hunger ratings or reduced energy/macronutrient intake. Emerging evidence suggests a potential improvement in insulin sensitivity following vitamin D that would impinge on food intake and substrate oxidation. However, the very few RCTs on supplemental vitamin D and energy balance have not explored postprandial avenues of the hormone's actions. Future efforts in this area need to define the threshold intake of these nutrients that would maximize metabolic and gastrointestinal outcomes. Such studies would provide a platform for endorsing the non-skeletal role of calcium and vitamin D in human pathophysiology.